ESTERIFICATION OF NYAMPLUNG (Calophyllum inophyllum) OIL WITH IONIC LIQUID CATALYST OF BMIMHSO4 AND MICROWAVES-ASSISTED (Jurnal Bahan Alam Terbarukan, 2018)
Nyamplung (Calophyllum inophyllum) oil contains high free fatty acid (FFA) that is 21.62%. Nyamplung oil can be utilized as raw material for biodiesel production. Microwave is a method of heating that is used intensively to speed up the production process. Ionic liquid has high catalytic activity, high selectivity, can be recycled and environmentally friendly. This study learned about the esterification of nyamplung oil with ionic liquid 1-Butyl-3-methylimidazolium hydrogen sulphate (BMIMHSO4) as catalyst and microwave-assisted. The purpose of this study is to obtain optimum condition of esterification process, with free fatty acid concentration (FFA) 2%. This study uses raw materials of nyamplung oil, methanol and BMIMHSO4 as catalyst. Equipment used in study was batch reactor equipped with temperature sensor with microwave heating system. The research variables studied were reaction temperature (50-70oC), molar ratio oil to methanol (1:30-1:60) and catalyst concentration (5-17.5%). The result of esterification reaction was analyzed by FFA (free fatty acid) content using titration analysis. The best free fatty acid (FFA) result was 1.92%, with molar ratio of oil to methanol was 1:40, catalyst concentration was 15% by weight and at 60oC for 120 min. The esterification ofÂ  nyamplung oil meets the criteria as biodiesel feedstock.